2010
DOI: 10.1017/s0047279410000905
|View full text |Cite
|
Sign up to set email alerts
|

Child Disability and the Dynamics of Family Poverty, Hardship and Financial Strain: Evidence from the UK

Abstract: Disabled children are significantly more likely to grow up in poverty than their nondisabled peers. We used longitudinal data from Waves 3-7 (2001Waves 3-7 ( -2005 of the UK Families and Children Study to explore the relationship between the presence of a disabled child in the family and poverty transitions. When compared to other families, families supporting a disabled child are more likely to be exposed to persistent or recurrent poverty, less likely to escape from an episode of poverty and more likely to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 33 publications
2
40
0
5
Order By: Relevance
“…With longitudinal data such as the FACS data, the effect of omitted variables can be taken into account by extending this model by incorporating a family-specific random effect into the modelling framework, also see (1,2,4). As a result, a statistical modelling approach is adopted, for the purposes of which, the variable: whether a family supports a disabled child (coded 1) or not (0) was regarded as the binary explanatory variable of primary interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With longitudinal data such as the FACS data, the effect of omitted variables can be taken into account by extending this model by incorporating a family-specific random effect into the modelling framework, also see (1,2,4). As a result, a statistical modelling approach is adopted, for the purposes of which, the variable: whether a family supports a disabled child (coded 1) or not (0) was regarded as the binary explanatory variable of primary interest.…”
Section: Discussionmentioning
confidence: 99%
“…Processes are by nature dynamic. It is important to address issues relevant to dynamics such as past behaviour, e.g., see (2) and feedback effects when investigating a process (4). Another example is the notion of ''cumulative inertia'' in which the tendency to move in the next time period from the current state to another decreases with the length of duration in the current state (14).…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, Mexican children from the poorest quintile of wealth have higher odds of having a SFD, which has also been described in other countries. 16 We found strong associations of SFD with maternal depression symptoms, violent or psychological discipline at home, and educational lag. A meta-analysis found that mothers of children with developmental disabilities are at higher risk of depression compared to mothers of children developing normally; 17 on the other hand, several studies report that children of mothers with depression have adverse consequences, such as behavior problems, deficits in cognitive performance and academic achievement.…”
Section: Discussionmentioning
confidence: 56%
“…income assistance and mental‐health services) than parents of children without IEPs. This finding may be indicative of trends suggesting higher levels of poverty among families of CWDs, which is related to increased eligibility and need for social services (Park et al ., ; Parish et al , ; Shahtahmasebi et al , ). It is also possible that parents of children with IEPs received information regarding available formal social service resources more consistently via the child's special education team.…”
Section: Discussionmentioning
confidence: 98%